2021
DOI: 10.1038/s41598-021-98142-1
|View full text |Cite
|
Sign up to set email alerts
|

Surface charge manipulation and electrostatic immobilization of synaptosomes for super-resolution imaging: a study on tau compartmentalization

Abstract: Synaptosomes are subcellular fractions prepared from brain tissues that are enriched in synaptic terminals, widely used for the study of neural transmission and synaptic dysfunction. Immunofluorescence imaging is increasingly applied to synaptosomes to investigate protein localization. However, conventional methods for imaging synaptosomes over glass coverslips suffer from formaldehyde-induced aggregation. Here, we developed a facile strategy to capture and image synaptosomes without aggregation artefacts. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Our findings lend support to the role of non-mutant human tau in synaptic dysfunction in AD. However, a recent report using super-resolution microscopy of fixed synaptosomes from WT (C57BL/6) mice observed significant colocalization of non-mutant murine tau with synaptophysin (marking pre-synaptic terminals) ( Bhattacharya et al, 2021 ). Interestingly, the authors noted tau also colocalized with the post-synaptic terminal marker protein post-synaptic density protein 95 (PSD-95), suggesting tau accumulates in both compartments of the synapse ( Bhattacharya et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings lend support to the role of non-mutant human tau in synaptic dysfunction in AD. However, a recent report using super-resolution microscopy of fixed synaptosomes from WT (C57BL/6) mice observed significant colocalization of non-mutant murine tau with synaptophysin (marking pre-synaptic terminals) ( Bhattacharya et al, 2021 ). Interestingly, the authors noted tau also colocalized with the post-synaptic terminal marker protein post-synaptic density protein 95 (PSD-95), suggesting tau accumulates in both compartments of the synapse ( Bhattacharya et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent report using super-resolution microscopy of fixed synaptosomes from WT (C57BL/6) mice observed significant colocalization of non-mutant murine tau with synaptophysin (marking pre-synaptic terminals) ( Bhattacharya et al, 2021 ). Interestingly, the authors noted tau also colocalized with the post-synaptic terminal marker protein post-synaptic density protein 95 (PSD-95), suggesting tau accumulates in both compartments of the synapse ( Bhattacharya et al, 2021 ). Subcellular fractionation analysis from mutant tau P 301 L mice showed that both murine tau and the human tau P 301 L were present in the synaptosomal fraction; however, tau P 301 L was preferentially distributed in the synaptosomal fraction while murine endogenous tau was more distributed in the cytosolic fraction ( Sahara et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%